2010
DOI: 10.5194/hess-14-2277-2010
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow sensitivity to climate and land cover changes: Meki River, Ethiopia

Abstract: Abstract. Impacts of climate and land cover changes on streamflow were assessed using a hydrological modeling. The precipitation runoff modeling system of the US Geological Survey was modified in order to consider wetlands as a separate hydrological response unit. Initial model parameters were obtained from a previously modeled adjacent catchment and subsequent calibration and validation were carried out. The model calibration and validation periods were divided into three. The calibration period was a five ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Several studies [9,21,48,49] have applied distributed models to study impacts of land use changes on hydrology as the models are intended to simulate the physical reality of the hydrological cycle, spatially and temporally, which is vital for effective land use planning and water management. The use of physically based semi-distributed model such as ACRU reduces the data requirements that would have been necessary for a fully distributed model, and justifies its application in a data-scarce region such as the Bonsa catchment in Ghana, West Africa.…”
Section: Dealing With Uncertainties In Land Use Change Impact Assessmmentioning
confidence: 99%
“…Several studies [9,21,48,49] have applied distributed models to study impacts of land use changes on hydrology as the models are intended to simulate the physical reality of the hydrological cycle, spatially and temporally, which is vital for effective land use planning and water management. The use of physically based semi-distributed model such as ACRU reduces the data requirements that would have been necessary for a fully distributed model, and justifies its application in a data-scarce region such as the Bonsa catchment in Ghana, West Africa.…”
Section: Dealing With Uncertainties In Land Use Change Impact Assessmmentioning
confidence: 99%
“…The results showed that a change of precipitation and potential evapotranspiration by 1% would cause a change of runoff by 2.1%-2.5% and 0.5%-1.0%, respectively. Legesse, et al [9] analyzed, quantitatively, the sensitivity of runoff to temperature and precipitation with a modified rainfall runoff modeling system of the US Geological Survey in the Meki River in Ethiopia. It was revealed in the result that the runoff would increase by 80% or decrease by 60%, respectively, if the precipitation increased or decreased by 20%, and the increase in temperature would cause the increase of evapotranspiration by 6% and the decrease of runoff by 13%.…”
Section: Introductionmentioning
confidence: 99%
“…Under this framework, the sensitivity of hydrological variables to climate change was studied all over the world (e.g. Chiew et al, 1995;Fontaine et al, 2001;Jones et al, 2006;Legesse et al, 2010;Ryu et al, 2011). However, because of the uncertainty of structure construction and parameters estimation of hydrological models, some different results would be concluded in the same basin with different models (Sankarasubramanian et al, 2001).…”
Section: Introductionmentioning
confidence: 99%